2011
DOI: 10.1038/jhg.2011.144
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of carrier frequencies of six autosomal-recessive Mendelian disorders in the Korean population

Abstract: Although many studies have been performed to identify mutations in Korean patients with various autosomal-recessive Mendelian disorders (AR-MDs), little is known about the carrier frequencies of AR-MDs in the Korean population. Twenty common mutations from six AR-MDs, including Wilson disease (WD), non-syndromic hearing loss (NSHL), glycogen storage disease type Ia (GSD Ia), phenylketonuria (PKU), congenital hypothyroidism (CH), and congenital lipoid adrenal hyperplasia (CLAH) were selected to screen for based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 35 publications
4
19
1
Order By: Relevance
“…In addition, we identified one carrier having two different heterozygous alleles, and one normal hearing having possibility to cause the HL. The frequencies of two mutations ( GJB2 c.235delC and c.2168A>G of the SLC26A4 gene) presented that the allele frequency of c.235delC mutation (0.52%) in normal hearing controls by other studies were very similar to the result of this study (0.51%) [10], [31][33], and the c.2168A>G mutation presented higher frequency than the other SLC26A4 mutations in this study and the previous studies in Koreans [9], [10], [31]. The c.439A>G, c.1149+3A>G, and c.1229C>T mutations of SLC26A4 were not detected in this study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, we identified one carrier having two different heterozygous alleles, and one normal hearing having possibility to cause the HL. The frequencies of two mutations ( GJB2 c.235delC and c.2168A>G of the SLC26A4 gene) presented that the allele frequency of c.235delC mutation (0.52%) in normal hearing controls by other studies were very similar to the result of this study (0.51%) [10], [31][33], and the c.2168A>G mutation presented higher frequency than the other SLC26A4 mutations in this study and the previous studies in Koreans [9], [10], [31]. The c.439A>G, c.1149+3A>G, and c.1229C>T mutations of SLC26A4 were not detected in this study.…”
Section: Discussionsupporting
confidence: 89%
“…Based on previous genetic studies of HL in the Korean population, we selected the seven most common mutations that lead to hereditary HL [8][12], [31]. Multiplex genotyping of these seven mutations was successfully performed using SNaPshot minisequencing, which produced accurate data and a detection rate of the mutations that was found to account for up to 40% of the causative mutant alleles associated with prelingual HL in Koreans [8].…”
Section: Discussionmentioning
confidence: 99%
“…Four studies from South Korea analyzed the frequency of the 3, 4, 6, or 7 most common mutations in South Korea in samples from 500, 476, 14,835, and 3,057 individuals, respectively. The corresponding genetic prevalence estimates were 1:3,000, 1:30,800, 1:7,500, and 1:27,000, respectively . These results have been taken to suggest a higher prevalence in South Korea than in the rest of the world, but selection biases may have hampered this conclusion.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we compared blood pressure between genetically confirmed patients with homozygous SLC26A4 mutation and controls with no inner ear anomalies such as EVA. Nonetheless, it is possible that subjects in the control group had a single mutant allele of SLC26A4, since this is present in 1.3% of the Korean population (16,17). Although we carried out a retrospective analysis of patients' medical records, blood pressure was reliably measured by experts using a standardized method, and comparisons were between individuals of the same ethnicity.…”
Section: Discussionmentioning
confidence: 99%